A Case of Inflammatory Pseudotumor of the Liver Mimicking Hepatocellular Carcinoma on EOB-MRI and PET. (27th May 2013) - Iguchi, Hiroyoshi; Yamazaki, Hitoshi; Tsunoda, Hidekazu; Takahashi, Yoshihito; Yokomori, Hiroaki
Abstract : A 71-year-old man was referred to us for investigation of a liver mass and adenomyomatosis of gallbladder. Findings on ethoxybenzyl diethylenetriamine-enhanced MRI (EOB-MRI) led to a presumptive diagnosis of a 1.5 cm hepatocellular carcinoma (HCC) in the right posterior lobe of the liver. Transcatheter arterial chemoembolization and radiofrequency ablation of the tumor were attempted. After 2 months, CT scan and EOB-MRI showed that the tumor had enlarged to 3 cm. Positron emission tomography (PET) confirmed abnormal metabolic activity with a high standardized uptake value of 7.3 in the lesion. These findings could indicate malignancy such as well-differentiated HCC or cholangiocarcinoma or a benign lesion such as hepatic abscess. Histopathological examination of a liver biopsy revealed a granuloma with many inflammatory cells, leading to a diagnosis of inflammatory pseudotumor of the liver. We report a rare case of hepatic inflammatory pseudotumor with enhancement on EOB-MRI and increased uptake on PET, mimicking HCC.